A method for preparing a high-activity, high-site-density fuel cell cathode catalyst

CN117691130BActive Publication Date: 2026-10-27INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311712282.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2026-10-27
Estimated Expiration
2043-12-13

AI Technical Summary

Technical Problem

[0004]本发明针对现有技术中存在燃料电池阴极催化剂匮乏的孔网络结构、无法精确控制的配位环境、较低的石墨化程度以及活性位点密度不足的问题,提出了一种高活性、高位点密度燃料电池阴极催化剂的制备方法

Benefits of technology

[0025](1)本发明得到的燃料电池阴极催化剂富含微孔与介孔结构。碱金属/碱土金属盐的引入在热解过程中通过毛细管现象渗透碳以促进多孔的形成。多孔碳的形成使催化剂的比表面积增加,有利于提高催化剂的催化面积。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117691130B_ABST
    Figure CN117691130B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of fuel cell cathode catalyst preparation, and particularly relates to a preparation method of a high-activity and high-site-density fuel cell cathode catalyst. The method comprises the following steps: mixing an alkali metal / alkaline earth metal salt, a transition metal salt, an oxidizing agent, a nitrogen source and a carbon source by using a one-pot method, and obtaining a precursor slurry through heating and concentration; performing heat treatment on the precursor slurry, and obtaining a carbonized sample through acid pickling, water washing and drying; and performing heat treatment on the carbonized sample to obtain the fuel cell cathode catalyst. The fuel cell cathode catalyst obtained by the method is rich in microporous and mesoporous structures, has a high graphitization degree, a high active transition metal and nitrogen coordination site density, and excellent catalytic performance, and has a strong application potential in the field of fuel cell devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell cathode catalyst preparation technology, specifically relating to a method for preparing a highly active fuel cell cathode catalyst with high site density. Background Technology

[0002] Driven by the trend towards cleaner and lower-carbon energy, electrochemical energy conversion technology, which converts the chemical energy contained in fuels and oxidants into electrical energy, plays a crucial role in achieving the goal of "carbon peaking and carbon neutrality." It represents an international technological frontier and industrial high ground related to national energy security and assurance systems, green and low-carbon development, and the growth of strategic emerging industries. Among these technologies, hydrogen fuel cells, with their advantages of cleanliness, safety, and high efficiency, are of great significance to my country's long-term development in both power generation and combined heat and power (CHP).

[0003] However, the oxygen reduction reaction (ORR) step in fuel cell devices requires noble metal catalysts to overcome the slow kinetics, which greatly increases the cost of the entire battery and hinders the large-scale commercial application of fuel cells. In existing research, transition metal-nitrogen co-doped carbon single-atom catalysts (M-NC, M=Mn,Fe,Co,Cu) are considered the most promising and reliable materials to replace noble metals. In the entire catalyst system, the coordination configuration of transition metal with four nitrogen atoms (MN4) is recognized as the main active site for catalyzing the oxygen reduction reaction. However, current M-NC catalysts still have many shortcomings: (1) Lack of rich pore structure. Too many micropores will limit the mass transfer and electron transfer of reactants, resulting in a decrease in the utilization rate of active sites. Too many macropores will reduce the specific surface area of ​​the catalyst, resulting in a low density of active sites and insufficient oxygen reduction performance. (2) The highly active coordination environment cannot be precisely designed. The coordination structure of metal and nitrogen (MN4) x There is a clear structure-activity relationship between M-NC catalysts and their activity. However, the synthesis of M-NC catalysts often involves heat treatment. During heat treatment, the coordination structure between metal and nitrogen becomes complex, making it impossible to accurately design the required high-activity, high-density MN4 sites. (3) The degree of graphitization is low. Heat treatment can lead to the collapse of the microstructure, which reduces the degree of graphitization of the catalyst, worsens its conductivity, and reduces its electron transport capacity. Summary of the Invention

[0004] This invention addresses the problems in existing fuel cell cathode catalysts, such as a lack of pore network structure, an uncontrollable coordination environment, a low degree of graphitization, and insufficient active site density. It proposes a method for preparing a highly active fuel cell cathode catalyst with high site density.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0006] A method for preparing a fuel cell cathode catalyst includes the following steps:

[0007] Step 1: Alkali metal / alkaline earth metal salts, transition metal salts, oxidants, nitrogen sources, and carbon sources are mixed in a one-pot process and then concentrated by heating to obtain a precursor slurry;

[0008] Step 2: The precursor slurry is heat-treated, followed by acid washing, water washing, and drying to obtain the carbonized sample;

[0009] Step 3: Heat-treat the carbonized sample to obtain the fuel cell cathode catalyst.

[0010] Preferably, the alkali metal / alkaline earth metal salt in step 1 is one of the chloride, carbonate, nitrate, and phosphate salts of lithium, sodium, potassium, magnesium, calcium, and strontium. This preferred method can prevent the loss of nitrogen source, enrich the pore network structure, and promote the formation of porous carbon.

[0011] Preferably, the transition metal salt in step 1 is one of the following: chloride salts, carbonates, nitrates, phosphates, sulfates, and acetates of iron, cobalt, manganese, and copper. This preferred embodiment can provide an active metal source for the cathode catalyst of a fuel cell.

[0012] Preferably, the nitrogen source in step 1 is one of aniline, o-phenanthroline, urea, 2-aminobenzylamine, and N-phenylethylenediamine. This preferred embodiment can provide an abundant nitrogen source for the fuel cell cathode catalyst.

[0013] Preferably, the oxidant in step 1 is ammonium persulfate. This preferred method is used for oxidative polymerization with a nitrogen source.

[0014] Preferably, the carbon source in step 1 is one of carbon black oxide, graphene oxide, or carbon nanotubes obtained through nitric acid treatment. This preferred method can improve the conductivity, hydrophilicity, and dispersibility of the catalyst.

[0015] Preferably, the molar ratio of alkali metal / alkaline earth metal salt to transition metal salt in step 1 is 0.125-2:1. The choice of this preferred molar ratio is based on the subsequent formation of the porous network structure and the density of MN4 active sites.

[0016] Preferably, in step 1, the molar ratio of the sum of alkali metal / alkaline earth metal salts and transition metal salts to the nitrogen source is 5.5-20:1. This preferred molar ratio is chosen based on the subsequent formation of active sites and the removal of residual metal salts.

[0017] Preferably, in step 2, the heat treatment temperature is 600-1100℃, the heat treatment time is 1-3 hours, and the heat treatment atmosphere is one of nitrogen, argon, or a hydrogen-nitrogen mixture. This preferred method can improve the conductivity of the catalyst, increase the degree of graphitization, structural integrity, and the formation of highly active sites.

[0018] Preferably, in step 2, the pickling process involves washing with a 1-3 mol / L hydrochloric acid solution for 24 hours. This preferred method can remove residual metal salts.

[0019] Preferably, in step 3, the heat treatment temperature is 900-1100℃, the heat treatment time is 2-4 hours, and the heat treatment atmosphere is nitrogen or argon. This preferred method can obtain a fuel cell cathode catalyst with a more stable structure and a better degree of graphitization.

[0020] A fuel cell cathode catalyst was prepared using the aforementioned method.

[0021] An electrode catalyst for a fuel cell is composed of the aforementioned fuel cell cathode catalyst.

[0022] An electrode for a fuel cell has a catalyst layer comprising the aforementioned electrode catalyst for a fuel cell.

[0023] A fuel cell having the aforementioned fuel cell electrode.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] (1) The fuel cell cathode catalyst obtained by this invention is rich in microporous and mesoporous structures. The introduction of alkali metal / alkaline earth metal salts promotes the formation of pores by permeating carbon through capillary action during pyrolysis. The formation of porous carbon increases the specific surface area of ​​the catalyst, which is beneficial to improving the catalytic surface area of ​​the catalyst.

[0026] (2) The fuel cell cathode catalyst obtained by this invention has a high degree of graphitization. This invention synthesizes alkali metal / alkaline earth metal salts and transition metal salts via a one-pot pyrolysis method. The alkali metal / alkaline earth metal salts melt during carbonization, forming a high-temperature solvent system. This allows for uniform heating of the catalyst precursor, thereby protecting its structure and increasing the degree of graphitization of the catalyst. Increased graphitization enhances electronic conductivity and corrosion resistance.

[0027] (3) In this invention, by introducing alkali metal / alkaline earth metal salts, the sites formed by the coordination of the transition metal center with oxygen reduction activity and nitrogen are more beneficial to the catalytic oxygen reduction reaction, thus obtaining a highly active fuel cell cathode catalyst.

[0028] (4) The catalyst obtained by this invention is a single-atom catalyst, in which the metal is maintained at the atomic scale, and no transition metal nanoparticles were observed under a high-resolution scanning transmission electron microscope. The atoms are exposed on the support as much as possible, so that each site can be fully utilized, which significantly improves the utilization rate of the catalyst.

[0029] (5) The present invention evaluates the obtained fuel cell cathode catalyst for fuel cell devices, and its performance has reached a level that is superior to that of commercial precious metal catalysts. Attached Figure Description

[0030] Figure 1 This is a synthesis diagram of the cathode catalyst for a fuel cell.

[0031] Figure 2 The image shows the XRD pattern of the LiFe-NC(0.5-1) catalyst in Example 1.

[0032] Figure 3 The image shows the HAADF-STEM image of the LiFe-NC(0.5-1) catalyst in Example 1.

[0033] Figure 4 The N2 isotherm adsorption-desorption curves of the LiFe-NC(0.5-1) catalyst in Example 1 are shown.

[0034] Figure 5 The image shows the XPS spectrum of the LiFe-NC(0.5-1) catalyst in Example 1.

[0035] Figure 6 The Raman spectrum of LiFe-NC (0.75-1) in Example 4 is shown.

[0036] Figure 7 ORR polarization curves of LiFe-NC(xy) (xy = 0.5-1, 0-1, 0.125-1, 0.75-1, 1-1, 2-1) in Examples 1-6;

[0037] Figure 8 TEM image of LiCo-NC in Example 7;

[0038] Figure 9 ORR polarization curves of LiCo-NC, NaCo-NC, KCo-NC, MgCo-NC, CaCo-NC, and SrCo-NC in Examples 7-12;

[0039] Figure 10 The graphs show the polarization curves of alkaline fuel cells using LiCo-NC and MgCo-NC as cathode catalysts in Examples 7 and 10.

[0040] Figure 11The ORR polarization curves of MgFe-NC, MgCo-NC, MgMn-NC, and MgCu-NC in Examples 13-16 are shown. Detailed Implementation

[0041] To facilitate understanding of the present invention, a more comprehensive description will be given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.

[0042] This invention provides a method for preparing a highly active fuel cell cathode catalyst with a high active site density, the synthesis diagram of which is shown below. Figure 1 As shown, a highly active catalyst capable of catalyzing the oxygen reduction reaction is obtained by concentrating alkali metal / alkaline earth metal salts and transition metal salts in a one-pot heating process, followed by further co-pyrolysis.

[0043] Example 1

[0044] This embodiment provides a method for preparing a fuel cell cathode catalyst using LiCl as an alkali metal / alkaline earth metal salt and FeCl3 as a transition metal salt, comprising the following steps:

[0045] Step 1: 44 mmol of LiCl, 88 mmol of FeCl3, 4 mmol of ammonium persulfate, and 16 mmol of 2-aminobenzylamine were added to 500 mL of 1.2 mol / L hydrochloric acid solution and stirred at room temperature for 3 h to obtain an oxidatively polymerized metal salt solution; graphene was added to excess concentrated nitric acid and stirred at 80 °C for 8 h, then washed with water and dried to obtain graphene oxide; 0.3 g of graphene oxide was added to 100 mL of aqueous solution and ultrasonically dispersed for 2 h to obtain dispersed carbon material; the dispersed carbon material was added to the metal salt solution, stirred at room temperature for 12 h, heated to 70 °C, and stirred continuously until concentrated to obtain a precursor slurry.

[0046] Step 2: Place the combustion boat containing the precursor slurry obtained in Step 1 into a tube furnace. Under an argon atmosphere, raise the temperature to 1000℃ at a heating rate of 20℃ / min and maintain it at 1000℃ for 1 hour. After cooling to room temperature, wash with 2mol / L hydrochloric acid solution for 24 hours, then wash with deionized water until neutral, filter and dry to obtain the carbonized sample.

[0047] Step 3: Place the carbonized sample obtained in Step 2 into a graphite crucible and maintain it at 1000℃ for 3 hours under an argon atmosphere at a heating rate of 20℃ / min. After cooling to room temperature, remove the sample to obtain a carbon-based fuel cell cathode catalyst co-doped with alkali metal / alkaline earth metal and transition metal-nitrogen, denoted as LiFe-NC(0.5-1).

[0048] Figure 2 The image shows the X-ray diffraction (XRD) pattern of the LiFe-NC(0.5-1) catalyst. The pattern shows that the catalyst only exhibits graphite peaks and no other impurity peaks, indicating that no nanoparticles or clusters are generated.

[0049] Figure 3 The image shows a high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of the LiFe-NC(0.5-1) catalyst. As can be seen from the image, no nanoparticles are present at high resolution, and the metal exists in the form of single atoms. This indicates that the present invention yields a single-atom catalyst, which greatly improves the utilization rate of metal sites.

[0050] Figure 4 The figure shows the N2 isotherm adsorption-desorption curve of the LiFe-NC(0.5-1) catalyst. It can be seen from the figure that the catalyst exhibits a type IV isotherm, indicating the formation of a large number of mesopores and a relatively uniform pore size distribution.

[0051] Figure 5 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the LiFe-NC(0.5-1) catalyst. Elemental analysis of the full spectrum revealed the presence of alkali metal Li and transition metal Fe.

[0052] Examples 2-6

[0053] Examples 2 to 6 are variations of Example 1, with the only difference being that the molar amount of LiCl in step 1 was replaced from 44 mmol to 0 mmol, 11 mmol, 66 mmol, 88 mmol, and 176 mmol, respectively. The resulting catalyst is denoted as LiFe-NC(xy) (xy = 0-1, 0.125-1, 0.75-1, 1-1, 2-1), as detailed in Table 1.

[0054] Table 1. Doping amount of LiCl in Examples 1-6

[0055] Example 1 LiFe-NC(0.5-1) 44 88 Example 2 LiFe-NC(0-1) 0 88 Example 3 LiFe-NC(0.125-1) 11 88 Example 4 LiFe-NC(0.75-1) 66 88 Example 5 LiFe-NC(1-1) 88 88 Example 6 LiFe-NC(2-1) 176 88

[0056] Table 2 shows the BET specific surface area of ​​the above catalysts. As can be seen from Table 2, the specific surface area of ​​the catalyst LiFe-NC(0-1) obtained without LiCl doping is only 956 m². 2 / g, while the specific surface area of ​​the catalyst increased significantly after doping with LiCl, with LiFe-NC(0.75-1) reaching a specific surface area of ​​1803m². 2 / g.

[0057] Table 2. BET specific surface area of ​​catalysts in Examples 1-6

[0058] Example 1 LiFe-NC(0.5-1) 1391 Example 2 LiFe-NC(0-1) 956 Example 3 LiFe-NC(0.125-1) 1433 Example 4 LiFe-NC(0.75-1) 1803 Example 5 LiFe-NC(1-1) 1629 Example 6 LiFe-NC(2-1) 1326

[0059] Figure 6 The Raman spectrum of LiFe-NC(0.75-1) shows that I D / I G The ratio reached 1.14, indicating that the content of graphitized carbon in the catalyst was higher than that of defective carbon, and the degree of graphitization of the sample was relatively high.

[0060] The catalysts obtained in Examples 1-6 were subjected to electrochemical testing under alkaline conditions. A conventional three-electrode system was used for the electrochemical testing on a CHI 760E electrochemical workstation. The specific testing procedure was as follows: 5 mg of catalyst, 100 μL of isopropanol, and 12 μL of Nafiion solution were mixed and ultrasonically prepared to obtain catalyst ink. The catalyst ink was then drop-coated onto a rotating ring-disk electrode (RRDE) to obtain the working electrode. A Hg / HgO electrode and a carbon rod electrode were used as the reference and counter electrodes, respectively. Under steady-state conditions, using a 20 mV potential step, the working electrode was swept from 1.0 V to 0 V, and ORR polarization curves were tested in O2-saturated 0.1 M KOH electrolyte. The test results are shown in [reference missing]. Figure 7 .

[0061] Figure 7 It can be observed that the performance of the LiCl-doped catalyst is significantly higher than that of the undoped catalyst, fully demonstrating the beneficial effects of the method proposed in this invention. Specifically, LiFe-NC(0.75-1) exhibits excellent oxygen reduction performance with an onset potential of 1.02 V vs. RHE and a half-wave potential of 0.93 V vs. RHE. This high oxygen reduction performance is mainly attributed to its larger specific surface area and higher degree of graphitization, which guides the formation of more FeN4 active sites.

[0062] Example 7

[0063] This embodiment provides a method for preparing a fuel cell cathode catalyst using Li2CO3 as an alkali metal / alkaline earth metal salt and CoCO3 as a transition metal salt, comprising the following steps:

[0064] Step 1: 66 mmol of Li₂CO₃, 88 mmol of CoCO₃, 4 mmol of ammonium persulfate, and 16 mmol of N-phenylethylenediamine were added to 500 mL of 1.2 mol / L hydrochloric acid solution and stirred at room temperature for 3 h to obtain an oxidatively polymerized metal salt solution; carbon black was added to excess concentrated nitric acid and stirred at 80 °C for 8 h, followed by washing with water and drying to obtain graphene oxide; 0.3 g of carbon black oxide was added to 100 mL of aqueous solution and ultrasonically dispersed for 2 h to obtain dispersed carbon material; the dispersed carbon material was added to the metal salt solution, stirred at room temperature for 12 h, heated to 70 °C, and stirred continuously until concentrated to obtain a precursor slurry.

[0065] Step 2: Place the combustion boat containing the precursor slurry obtained in Step 1 into a tube furnace. Under an argon atmosphere, raise the temperature to 900℃ at a heating rate of 20℃ / min and maintain it at 900℃ for 2 hours. After cooling to room temperature, wash with 1mol / L hydrochloric acid solution for 24 hours, then wash with deionized water until neutral, filter and dry to obtain the carbonized sample.

[0066] Step 3: Place the carbonized sample obtained in Step 2 into a graphite crucible and maintain it at 900℃ for 2 hours under an argon atmosphere at a heating rate of 20℃ / min. After cooling to room temperature, remove the sample to obtain a carbon-based fuel cell cathode catalyst co-doped with alkali metal / alkaline earth metal and transition metal-nitrogen, denoted as LiCo-NC.

[0067] Figure 8 The image shows a transmission electron microscope (TEM) image of the LiCo-NC catalyst. No nanoparticles were found in the image, indicating that no impurity phase was present.

[0068] Examples 8-12

[0069] Examples 8-12 are variations of Example 7, differing only in that Li2CO3 in step 1 is replaced with Na2CO3, K2CO3, MgCO3, CaCO3, and SrCO3, respectively. The resulting catalysts are denoted as NaCo-NC, KCo-NC, MgCo-NC, CaCo-NC, and SrCo-NC. Table 3 shows the BET specific surface areas of the catalysts obtained in Examples 7-12, as detailed in Table 3.

[0070] Table 3. BET specific surface area of ​​catalysts in Examples 7-12

[0071] Example 7 LiCo-NC 1889 Example 8 NaCo-NC 1636 Example 9 KCo-NC 1577 Example 10 MgCo-NC 1919 Example 11 CaCo-NC 1826 Example 12 SrCo-NC 1773

[0072] Table 3 shows that the specific surface area of ​​the catalysts obtained in Examples 7-12 can all reach 1500 m². 2The presence of alkali metals or alkaline earth metals at a concentration of over / g fully demonstrates that doping with alkali metals or alkaline earth metals has a positive effect on increasing the specific surface area of ​​the catalyst.

[0073] Figure 9 The ORR polarization curves of LiCo-NC, NaCo-NC, KCo-NC, MgCo-NC, CaCo-NC, and SrCo-NC catalysts are shown. All of these catalysts exhibit excellent oxygen reduction performance and are characterized by high oxygen reduction activity.

[0074] The catalyst was evaluated in an alkaline fuel cell device. The specific testing procedure was as follows: a commercial platinum-carbon catalyst was used as the anode catalyst in the fuel cell, with a platinum loading of 0.1 mg / cm³. 2 LiCo-NC and MgCo-NC catalysts were used as cathode catalysts in the fuel cell, with a catalyst loading of 3 mg / cm³. 2 Using PiperION-A20-HCO3 - As an anion exchange membrane; at 5cm 2 Under the battery clamp, the battery temperature was set to 80℃, the anode hydrogen flow rate was 1000 sccm, the cathode oxygen flow rate was 1000 sccm, and the relative humidity was 100%. The voltage range for polarization curve testing was from open circuit voltage to 0.2V, with a voltage step size of 0.05V, and each voltage step was maintained for 1 minute. Figure 10 The figures shown are polarization curves of alkaline fuel cells using LiCo-NC and MgCo-NC as cathode catalysts in Examples 7 and 10. The figures demonstrate that the maximum power density can reach 1 W / cm². 2 The above represents an extremely high level among non-precious metal catalysts currently used as cathode catalysts in alkaline fuel cells.

[0075] Example 13

[0076] This embodiment provides a method for preparing a fuel cell cathode catalyst using Mg(NO3)2 as an alkali metal / alkaline earth metal salt and Fe(NO3)3 as a transition metal salt, comprising the following steps:

[0077] Step 1: 100 mmol of Mg(NO3)2, 80 mmol of Fe(NO3)3, 3.8 mmol of ammonium persulfate, and 15 mmol of aniline were added to 500 mL of 1.2 mol / L hydrochloric acid solution and stirred at room temperature for 3 h to obtain an oxidatively polymerized metal salt solution; carbon nanotubes were added to excess concentrated nitric acid and stirred at 80 °C for 8 h, then washed with water and dried to obtain graphene oxide; 0.3 g of carbon nanotube oxide was added to 100 mL of aqueous solution and ultrasonically dispersed for 2 h to obtain dispersed carbon material; the dispersed carbon material was added to the metal salt solution, stirred at room temperature for 12 h, heated to 80 °C, and stirred continuously until concentrated to obtain a precursor slurry.

[0078] Step 2: Place the combustion boat containing the precursor slurry obtained in Step 1 into a tube furnace. Under a nitrogen atmosphere, raise the temperature to 700℃ at a heating rate of 20℃ / min and maintain it at 700℃ for 2 hours. After cooling to room temperature, wash with 1mol / L hydrochloric acid solution for 24 hours, then wash with deionized water until neutral, filter and dry to obtain the carbonized sample.

[0079] Step 3: Place the carbonized sample obtained in Step 2 into a graphite crucible and maintain it at 700℃ for 3 hours under a nitrogen atmosphere at a heating rate of 20℃ / min. After cooling to room temperature, remove the sample to obtain a carbon-based fuel cell cathode catalyst co-doped with alkali metal / alkaline earth metal and transition metal-nitrogen, denoted as MgFe-NC.

[0080] Examples 14-16

[0081] Examples 14-16 are variations of Example 13, differing only in that Fe(NO3)3 in step 1 is replaced with Co(NO3)2, Mn(NO3)2, and Cu(NO3)2, respectively. The resulting catalysts are denoted as MgCo-NC, MgMn-NC, and MgCu-NC. Table 4 shows the metal content (wt.%) of the catalysts obtained in Examples 13-16 as determined by inductively coupled plasma atomic divergence spectrometry (ICP-OES). See Table 4 for details.

[0082] Table 4. Metal content of catalysts in Examples 13-16

[0083]

[0084] The relatively low content of alkaline earth metal Mg shown in Table 4 indicates that the alkali metal / alkaline earth metal salts, after forming a molten salt protective catalyst structure during pyrolysis, can be largely removed through acid washing. The content of transition metals Fe, Co, Mn, and Cu reaches 7wt.%-10wt.%, achieving a high loading of active metals, confirming that the method provided in this invention can obtain fuel cell cathode catalysts with high MN4 active site density.

[0085] Figure 11 The ORR polarization curves of the MgFe-NC, MgCo-NC, MgMn-NC, and MgCu-NC catalysts in Examples 13-16 are shown in alkaline conditions. All catalysts exhibit excellent catalytic performance, confirming that the method provided by this invention can achieve highly active fuel cell cathode catalysts.

[0086] The above description is only for better explaining the embodiments of the present invention and is not intended to limit them. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.

Claims

1. A method for preparing a fuel cell cathode catalyst, characterized in that, Includes the following steps: Step 1: Alkali metal / alkaline earth metal salts, transition metal salts, oxidants, nitrogen sources, and carbon sources are mixed in a one-pot process and then concentrated by heating to obtain a precursor slurry; Step 2: The precursor slurry is heat-treated, followed by acid washing, water washing, and drying to obtain the carbonized sample; Step 3: Heat-treat the carbonized sample to obtain the fuel cell cathode catalyst; In step 1, the molar ratio of alkali metal / alkaline earth metal salt and transition metal salt is 0.125-2:1; the molar ratio of metal salt to nitrogen source is 5.5-20:

1. In step 1, the alkali metal / alkaline earth metal salt is one of the chloride, carbonate, nitrate, and phosphate salts of lithium, sodium, potassium, magnesium, calcium, and strontium; the transition metal salt is one of the chloride, carbonate, nitrate, phosphate, sulfate, and acetate salts of iron, cobalt, manganese, and copper; the nitrogen source is one of aniline, o-phenanthroline, urea, 2-aminobenzylamine, and N-phenylethylenediamine; and the carbon source is one of carbon black oxide, graphene oxide, and carbon nanotube oxide. In step 2, the heat treatment temperature is 600-1100℃, the heat treatment time is 1-3h, and the heat treatment atmosphere is one of nitrogen, argon, or a hydrogen-nitrogen mixture. In step 3, the heat treatment temperature is 900-1100℃, the heat treatment time is 2-4 hours, and the heat treatment atmosphere is nitrogen or argon.

2. The method for preparing a fuel cell cathode catalyst according to claim 1, characterized in that, In step 2, the pickling process involves washing with a 1-3 mol / L hydrochloric acid solution for 24 hours.

3. A cathode catalyst for a fuel cell, characterized in that, It is prepared using the method described in any one of claims 1 to 2.

4. An electrode catalyst for a fuel cell, characterized in that, It is composed of the fuel cell cathode catalyst as described in claim 3.

5. An electrode for a fuel cell, characterized in that, It has a catalyst layer comprising the electrode catalyst for fuel cells as described in claim 4.

6. A fuel cell, characterized in that, It has the electrode for a fuel cell as described in claim 5.

Citation Information

Patent Citations

  • High-nitrogen-content non-noble metal monatomic catalyst as well as preparation method and application thereof

    CN114713255A

  • Non-precious metal catalysts

    US20140045098A1